Exercise tolerance and physical activity in children with most common cardiovascular diseases - Shtrakh, Kateryna; Rak, Larysa; Shevchenko, Natalia; Odigbo, Shalom (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Summary: The cardiovascular system is actively involved in the adaptive reactions of the body. The deterioration of adaptive processes decreases the functional capabilities of the heart. Arterial hypertension is often known as the main cause of fatal cardiovascular events in adults. The aim of our study was to determine the adaptive capabilities of the cardiovascular system of adolescents with non-inflammatory cardiomyopathies depending on physical activity’s level. There were examined 92 patients with arterial hypertension and connective tissue dysplasia, the mean age was 15,4 ± 1,33 years. In order to study tolerance to the minimum physical activity and its influence on the state of the cardiovascular system in children, the Ruffier test was conducted. The vegetative reactions of central nervous system were performed by the orthostatic test. The functional state of the myocardium was assessed according to the results of the ultrasonic Doppler study of the heart. As a result of the study, it was found that in connective tissue dysplasia and arterial hypertension adaptation mechanisms were affected, accompanied by a weakening of cardiac functional capabilities. This happens against the background of a decrease in the functioning of the left ventricle. These changes are accompanied by hyperactivation of the autonomic nervous system in patients in the studied groups. The physical activity and physical development of children affect the adaptive capabilities of a growing organism. This is due to the fact that the children in group with AH and CTD were less physically active than children without myocardial pathology. Adolescents who showed the reduced results of Ruffier's test and had regular sports sections need change of a mode of training and further inspection.